Investigation of students’ pro-environmental behavior around Indonesia’s new capital city - Atin Nuryadin; Lambang Subagiyo; Nurul Fitriyah Sulaeman; Syayidah Dinurrohmah; Putri Sri Rahmawati (Institute of Advanced Engineering and Science, 2023)
The relocation of the capital city of Indonesia needs the utmost support for its sustainability. This paper is an explorative study on the pro-environmental behavior (PEB) of students from the buffer cities closest to the new capital city. Data were collected using a questionnaire based on the two major environmental values and appreciation instruments. The questionnaire contained 21 items that measured PEB in relation to three aspects: preservation, utilization, and appreciation. Data were collected from 280 junior high school students who participated in an online questionnaire. The data analysis used descriptive statistics and correlations. Utilization was identified as having the highest score among the three aspects, indicating that most students in the buffer cities hold exploitative utilitarian preferences for nature. Interventional education programs are needed to reduce human over-exploitation of the environment and prevent further environmental degradation. The highest correlation was found between appreciation and preservation, which was significant and positive. Gender was not a variable that affected PEB. However, the location of the buffer cities was the factor that showed the most significant differences in the scores. Our results could provide relevant insights for the design of environmental education to support the sustainability of Indonesia’s new capital city.